The role of social work to reduce family problems for those who are behind in school: theory review - Alshehri, Hanan Dhaher Ali (Journal of Humanities & Social Sciences, 2022)
This study focused on identifying the professional role of social work to reduce the family problems of those who are behind in school, which represents a main objective of the research, and several sub-goals emerged from it, represented in: Identifying the problem of those who are behind in school (the concept, causes and methods of treatment) and identifying the family problems of those who are behind in school, knowing the impact of these problems on the lives of children, in addition to knowing the role of school social work, and determining the role of the school social worker in facing the problem of those who are behind in school. Through a theoretical review using the descriptive approach, one of its types is desk research based on published data and information, by referring to the available Arab and foreign scientific sources. Based on the information collected, the most important results were summarized in the following: The school field is a basic field of social work practice, and that the reasons for students’ those who are behind in school are due either to environmental or subjective reasons, and family and social factors are the most common factors in the occurrence of a problem. Those who are behind in school, and family problems may directly or indirectly affect the lives of children, and it is possible to treat those who are behind in school either by medical, psychological, educational or social treatment, and the roles and responsibilities of the school social worker are many and varied. The current study reached several recommendations, including: Strengthening the role of social workers within the school and empowering them comprehensively, establishing a partnership between schools and family counseling centers to ensure rapid solutions, holding virtual classes via the Internet for those who suffer from chronic diseases and who find it difficult to attend due to their health condition.